Virtual reality speaking application utilisation in combatting presentation apprehension / Siti Maftuhah Damio and Qistina Ibrahim. - Damio, Siti Maftuhah; Ibrahim, Qistina (2018)
Virtual Reality (VR) application in the field of education has been an ongoing endeavour. It is believed that VR provides an opportunity for students to learn in a real situation through the exposure of artificially created reality and the use of visual which improves the learning by enhancing study focus (Piovesan, Passerion and Pereira, 2012). The accessibility to VR is made even easier with the invention of wireless VR. Incorporating this technology in language learning is a logical step, particularly in combatting students’ apprehension to carry out presentations. Thus, the focus of this study is to investigate UiTM Faculty of Education TESL postgraduates’ attitude in using virtual reality speaking application to ease their presentation apprehension. A mixed-method study is adopted by incorporating both quantitative (questionnaire) and qualitative (interviews) approaches. A purposive sampling of twenty-four TESL postgraduates is used to gather data which was then analysed using SPSS version 23 for the questionnaire and thematic analysis for the interview. Descriptive statistics is used to present the findings. The findings show that the participants have a limited knowledge of VR speaking application. Nonetheless, they are very interested and motivated to use the application as part of their presentation preparation especially in easing their apprehension. VR speaking application provides a crucial connection in improving oral presentations skills, but it is not the best approach for teachers to develop speaking skills. As this study is based on the respondents’ perceptions, future work is necessary to statistically study the effectiveness of VR speaking technology in language learning as well as investing if any significant relationship is formed between VR speaking application and language learning and teaching variables.